Performance of Single Comb White Leghorn Layers Fed with Aloe vera, Curcuma longa (Turmeric) and Probiotic - Moorthy, M.; Saravanan, S.; Mehala, C.; Ravi, S.; Ravikumar, M.; Viswanathan, K.; Edwin, S.C. (International Journal of Poultry Science, 2009)
Two hundred and eighty commercial layer chicks belonging to single hatch were purchased from local hatchery, wing banded, weighed and randomly allotted into seven treatment groups with four replicates of ten chicks each. The chicks were reared in cages in a gable roofed, open sided house. All the chicks were provided with uniform floor, feeder and waterer space and were reared under standard management conditions throughout the experimental period. The experimental diet was formulated according to the standards prescribed in Bureau of Indian Standards (B.I.S., 1992). The treatment groups were T1-Control; T2-0.1% aloe vera; T3-0.1% turmeric; T4-0.1% probiotic; T5-0.1% aloe vera + 0.1% turmeric; T6-0.1% aloe vera + 0.1% probiotic and T7-0.1% turmeric + 0.1% probiotic powder. There was no significant difference in feed consumption. Hen housed egg production, hen day egg production and return over feed cost differ significantly after 40 weeks of age during the experimental period. The overall mean per cent broken eggs differ significantly (p